Effect of Prior Microstructure and Heating Rate on the Austenitization Kinetics of 39NiCrMo3 Steel. Issue 5 (8th December 2016) - Spezzapria, Mattia; Settimi, Alessio G.; Pezzato, Luca; Novella, Michele F.; Forzan, Michele; Dughiero, Fabrizio; Bruschi, Stefania; Ghiotti, Andrea; Brunelli, Katya; Dabalà, Manuele
Abstract : The formation of austenite from three different prior microstructures is studied in a 39NiCrMo3 steel, which, indeed, is widely used in the industry, especially for induction heating treatments, due to its resistance to thermal cracking. The starting microstructure of sorbite with fine carbides, sorbite with coarse carbides and stress‐relieved martensite is examined in detail by optical microscopy, scanning electron microscopy, and Vickers microhardness measurements. Dilatometric tests are performed employing different heating rates spanning in the 100–800 °C s −1 range in order to assess the kinetics of the austenitic transformation. The experimental results are compared and critically linked in order to determine the fundamental factors governing the austenite formation when using high heating rates. The formation of austenite from sorbite with coarse and fine carbides is observed to occur in two consecutive stages: (i) cementite dissolution and (ii) ferrite to austenite transformation. The start and finish temperature of austenitic transformation increase with heating rate. For stress‐relieved martensitic microstructure, instead, the α' to γ transformation can take place through two different mechanisms: diffusive at low heating rates and displacive at high heating rate. Critical points of austenite formation initially increase with heating rate, reach a maximum and then decrease at high heating rate. Abstract : In this work, the austenitization of the low alloy steel 39NiCrMo3 is studied in order to develop the continuous heating transformation diagrams (CHT) for different prior microstructures, varying the heating rate. It is shown that prior microstructure and also heating rate significantly affect the kinetics of austentization processes. Moreover the various mechanism of austenite formation for each microstructures are described.